BUSINESS CENTER ROLE AS EFFORT LEARNING ENTREPRENEURSHIP IN THE ERA OF THE COVID-19 PANDEMIC STUDY CASE AT SMK MUHAMMADIYAH 2 MALANG - Ningsih, Fitri Amaliyahni (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
SMK Muhammadiyah 2 Malang is one of the vocational high school in Malang City which has a marketing laboratory in the form of a business center called SMUD’S Mart. SMUD’S Mart is a place for student practice that is designed in such a way as to provide students with an overview of the business world. SMUD’S Mart is also expected to be able to create vocational graduates who are ready to work based on their competencies. In the COVID-19 conditions that require online learning, it is hoped that the business center will remain a practice-based entrepreneurship learning facility for students so that it can motivate students to become entrepreneurs. The purpose of this study was to find out (1) planning, policy, organizing and controlling business centers (2) school’s efforts to utilize business center as an effort to learn entrepreneurship (3) practice-based learning processes in the era of the COVID-19 pandemic at SMK Muhammadiyah 2 Malang. This research uses descriptive qualitative method. Data collection techniques using observation, interviews and documentation. The results of this study show that (1) the management of SMUD’S Mart is very well organized, supported by the management of SMUD’S Mart which consists of a young workforce (2) the theoretical learning obtained by students is less than optimal and SMUD’S Mart branding is lacking, so practical efforts online selling is one of the solutions from the department (3) the practice-based entrepreneurship learning process at SMK Muhammadiyah 2 Malang is only at SMUD’S Mart. The advice given by the researcher is to maximize student practice by selling products initiated by the students themselves, so that students will learn how to buikd a business with the capital and ideas they have.